2006
DOI: 10.1002/pola.21521
|View full text |Cite
|
Sign up to set email alerts
|

Bipyridinophane‐containing conjugated polymers modulated with an intramolecular aromatic CH/π interaction

Abstract: Bipyridinophane-fluorene conjugated copolymers have been synthesized via Suzuki and Heck coupling reactions from 5,8-dibromo-2,11-dithia[3]paracyclo [3](4,4 0 )-2,2 0 -bipyridinophane and suitable fluorene precursors. Poly [2,7-(9,9-dihexylfluorene)-coalt-5,8-(2,11-dithia[3]paracyclo [3](4,4 0 )-2,2 0 -bipyridinophane)] (P7) exhibits large absorption and emission redshifts of 20 and 34 nm, respectively, with respect to its planar reference polymer Poly[2,7-(9,9-dihexylfluorene)-co-alt-1,4-(2,5-dimethylbenzene)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…This extraction of HPA would lead to a decrease in proton conductivity and durable lifetime in fuel cell systems. 12 Thus the retention of HPA was considered as one of the key parameters on determining the feasibility of the composite membranes used in the fuel cell systems.…”
Section: Stability Of Hpa In the Composite Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…This extraction of HPA would lead to a decrease in proton conductivity and durable lifetime in fuel cell systems. 12 Thus the retention of HPA was considered as one of the key parameters on determining the feasibility of the composite membranes used in the fuel cell systems.…”
Section: Stability Of Hpa In the Composite Membranesmentioning
confidence: 99%
“…11 Heteropolyacid (HPA), such as phosphotungstic acid (PWA), is one of the attractive inorganic additives because of their high proton conductivity and thermal stability in crystalline form. 12,13 Fenton and coworkers 14 recast the Nafion/HPA composite for H 2 /O 2 fuel cell and found that the HPA could increase the conductivity of the membrane. Staiti et al 15 and Shao et al 16 evaluated PWA-doped composite silica/Nafion/PWA membranes for hightemperature DMFCs (145 C).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of transition metals on the fluorescence of polymers 7a and 7b, which contain bipyridinophane units, has been investigated in THF solution [165]. The fluorescence of both polymers was quenched by Cu 2 þ , Co 2 þ , and Ni 2 þ ions.…”
Section: Conducting Polymers Modified With Receptor Groups J371mentioning
confidence: 99%
“…Recently, polyimides containing benzimidazole moieties were prepared by two-step procedure using 6,4 0 -diamino-2phenylbenzimidazole (BIA) as a monomer, resulting in good mechanical properties. 19 In this work, we developed a new synthesis route to produce the diamine monomer containing benzimidazole units, BIA. It was easily synthesized via formation of imidazole ring in NMP.…”
Section: Introductionmentioning
confidence: 99%
“…As a comparison, the synthesis of BIA was very complicated via amidation and ring formation, reported in the past. 19,20 Based on BIA, a series of polyimides were prepared by the reaction of diamine with various dehydrates using a traditional two-step procedure. Tough and flexible polyimide films with good thermal stability and mechanical properties were expected to obtain by introducing benzimidazole units into the main chains of polyimides.…”
Section: Introductionmentioning
confidence: 99%